Impact of the Ketogenic Diet on Linear Growth in Children: A Single-Center Retrospective Analysis of 34 Cases - Cinzia Ferraris; Monica Guglielmetti; Ludovica Pasca; Valentina De Giorgis; Ottavia Eleonora Ferraro; Ilaria Brambilla; Alessandro Leone; Ramona De Amicis; Simona Bertoli; Pierangelo Veggiotti; Anna Tagliabue (2019)
Data on the impact of the ketogenic diet (KD) on children’s growth remain controversial. Here, we retrospectively investigated the occurrence of linear growth retardation in 34 children (47% males; age range: 2−17 years) diagnosed with drug-resistant epilepsy (DRE; n = 14) or glucose transporter type 1 deficiency syndrome (GLUT1-DS; n = 20) who had been treated with the KD for 12 months. The general characteristics of children with and without growth retardation were also compared. All participants received a full-calorie, traditional KD supplemented with vitamins, minerals, and citrate. Most children (80%; 11/14 in the DRE subgroup and 16/20 in the GLUT1-DS subgroup) treated with the KD did not show growth retardation at 12 months. Although participants with and without delay of growth did not differ in terms of baseline clinical characteristics, dietary prescriptions, or supplementation patterns, marked ketosis at 12 months tended to occur more frequently in the latter group. Altogether, our results indicate that growth retardation may occur in a minority of children treated with the KD. However, further research is required to identify children at risk and to clarify how increased ketones levels may affect endocrine pathways regulating growth during KD administration.